Drug‐Induced Mitochondrial Dysfunction 2008
DOI: 10.1002/9780470372531.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Oxygen Sensors, the Oxygraph, and High‐Resolution Respirometry to Assess Mitochondrial Function

Abstract: Introduction 2. Polarographic oxygen sensor and traditional oxygraphy 3. High-resolution respirometry: the Oxygraph-2k 3.1. Calibration of polarographic oxygen sensors and oxygen concentration in respiration media at air saturation 3.2. From oxygraph slopes to respiratory flux corrected for background effects 4. Phosphorylation control protocol with intact cells 4.1. Titration steps of the PC protocol 4.2. Experimental example for the PC protocol 4.3. Flux control ratios from the PC protocol 5. Intact cells, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 64 publications
1
73
0
4
Order By: Relevance
“…Assessing O 2 consumption (cellular respiration) in nonpermeabilized cells using polarographic oxygen sensors accurately measures mitochondrial function. 43 We found that AMA-treated cells significantly decreased routine respiration even 24 h after treatment ( Fig. 6A; p < 0.01).…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 85%
“…Assessing O 2 consumption (cellular respiration) in nonpermeabilized cells using polarographic oxygen sensors accurately measures mitochondrial function. 43 We found that AMA-treated cells significantly decreased routine respiration even 24 h after treatment ( Fig. 6A; p < 0.01).…”
Section: Ama Increases Mitochondrial Omentioning
confidence: 85%
“…All assays were conducted at 378C, selected as a representative of thoracic temperature of the studied hymenopteran species in flight (A. mellifera [44], B. impatiens [16], V. vulgaris [45]). Electrodes were calibrated daily, and background rates were assessed every two weeks [46]. Substrates and inhibitors were added successively with Hamilton syringes following different protocols (see next paragraph), and concentrations used were based on [47] or adjusted to saturating levels during preliminary experiments.…”
Section: (B) Flight Muscle Fibres Isolation and Permeabilizationmentioning
confidence: 99%
“…Approximately 8 · 10 6 cells were added to each of the two Oxygraph-2k chambers and tested for the effect of treatment on ROUTINE respiration (R; no additions), LEAK respiration (L; oligomycin, inhibiting ATP synthesis), and ETS capacity (E; maximum noncoupled respiration at optimum uncoupler concentration) in LHON cells (Gnaiger, 2008;Iyer et al, 2009b;Pesta and Gnaiger, 2012). The difference (R -L) represents net respiration coupled to ATP synthesis.…”
Section: Mitochondrial Gene Therapy Improved Respiration In Lhon Cellsmentioning
confidence: 99%
“…As the patient had died of respiratory and cardiac failure, we conducted our first experiment to analyze the effect of mitochondrial gene therapy on mitochondrial respiration. Approximately 8 · 10 6 intact cells were added to each of the two respiration chambers and tested for the effect of treatment on ROUTINE, LEAK, and ETS respiration in LS and cells over 3 weeks (Gnaiger, 2008;Iyer et al, 2009b;Pesta and Gnaiger, 2012). Treatment of LS fibroblasts with donor mtDNA + rhTFAM increased ROUTINE respiration compared with buffer CTL or treatment with rhTFAM alone (Fig.…”
Section: Mitochondrial Gene Therapy Improved Respiration and Restoredmentioning
confidence: 99%